ROLE OF CAKRAMARDA BIJA (CASSIA TORA LINN) ON DADRU KUSHTA: A RANDOMIZED CONTROLLED GROUP TRIAL - Saini, *Jeeta Ram; Kumar Mandal, Sisir (International Journal of Ayurveda and Pharma Research, 2017)
In Ayurveda all the skin disease considered in Kushta. Which are further categorised in to Maha Kushta and Kshudra Kushta. Kushta is produced invariably by the vitiation of the seven factors i.e. 3 Dosha and 4 Dushya. When the vitiated Dosha provoke the four body elements and if this derangement of seven Dravya is not cared to, a disease is formed inside the body which manifests itself on outermost part of the body. Acarya Caraka has depicted Dadru as a Kshudra Kushta. As per its definition, the reddish coloured Pidika in the form of Mandala with elevated borders and itching is known as Dadru. The object was to assess the Vishaghna, Dadrughna, Kushtaghna effect of Cakramarda Bija Curna in the management of Dadru Kushta. Material and methods: For the present study 80 patients of Dadru were registered and randomly divided into following 2 groups. Group A: In this group, Edagajadi Lepa for the local application with Kanji and Cakramarda Bija Curna as an internal use. 40 patients were enrolled in this group out of which 6 patients dropped out and only 34 patients completed the trial. Group B: Edagajadi lepa for the local application with Kanji 40 patients were enrolled in this group out of which 4 patients dropped and only 36 patients completed the trial. Statistical analysis used: Data analysis of non-parametric variables by using Wilcoxon matched paired test. Results: In both group maximum relief observed in symptoms as Kandu, Visarpana on body, Visarpana on lesion and Raga. Conclusion: On conducting the clinical study it was concluded that both trial drugs are effective in the management of Dadru.